The Impact of Parental Verbal Abuse on Adolescent Decision-Making in North Binjai, Indonesia - Putri, Sabrina Dwi; Dinata Saragi, Muhammad Putra (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
Verbal abuse by parents can significantly affect adolescents' decision-making abilities. This qualitative study investigated the experiences of five adolescents aged 16-20 years in North Binjai, Indonesia who were subjected to verbal violence by their parents. Using Simon's Decision-Making Model, this study explored how cognitive, emotional, and self-confidence factors interact with parenting styles and cultural norms to shape adolescents' decision-making process. In-depth interviews, observations, and additional documentation revealed that verbal abuse, manifested through yelling, harsh language, and belittling, has substantial negative effects on adolescents' cognitive processes, emotional stability, and self-confidence. These factors are essential for effective decision making, particularly in the stages of intelligence, design, choice, and implementation. However, two of the five adolescents exhibited relatively stronger decision-making abilities, suggesting that social support, personal coping strategies, and other protective elements may help alleviate some adverse effects associated with authoritarian parenting and verbal abuse. The study highlighted the importance of evaluating and reconsidering child-rearing methods in the context of adolescent decision-making, especially in cultures where verbal abuse is often considered a